Accurate Runout Measurement for HDD Spinning Motors and Disks - Quan JIANG; Chao BI; Song LIN (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2010)
As hard disk drive (HDD) areal density increases, its track width becomes smaller and smaller and so is non-repeatable runout. HDD industry needs more accurate and better resolution runout measurements of spinning spindle motors and media platters in both axial and radial directions. This paper introduces a new system how to precisely measure the runout of HDD spinning disks and motors through synchronously acquiring the rotor position signal and the displacements in axial or radial directions. In order to minimize the synchronizing error between the rotor position and the displacement signal, a high resolution counter is adopted instead of the conventional phase-lock loop method. With Laser Doppler Vibrometer and proper signal processing, the proposed runout system can precisely measure the runout of the HDD spinning disks and motors with 1 nm resolution and 0.2% accuracy with a proper sampling rate. It can provide an effective and accurate means to measure the runout of high areal density HDDs, in particular the next generation HDDs, such as, pattern media HDDs and HAMR HDDs.